An overview on the use of enhanced efficiency nitrogen fertilizers in irrigated Mediterranean agriculture - Tomaz, Alexandra (2017)
In Mediterranean regions climate change has led to greater inter and intra-annual rainfall irregularity, causing an increase in the demand for irrigation water, inevitably accompanied by an increase in the use of others resources like nitrogen fertilizers. Nitrogen is associated with negative economic and environmental impacts, which requires particularly important decision-making in terms of its application to meet crop needs. The agronomic efficiencies of water and nitrogen vary widely among different environments and can be modified due to management practices. However, some studies suggest that agronomic practices alone are not sufficient to entirely avoid nitrogen losses. In irrigated cropping systems, where classical nitrogen fertilizers are partially applied through irrigation water, Enhanced Efficiency Fertilizers (EEF), namely slow release and controlled release products, and nitrification inhibitors, have the potential to reduce nitrogen losses, contributing to higher resource-use efficiencies. This work aims to provide an overview of the possibilities of successfully using this type of fertilizers in irrigated agriculture, especially in Mediterranean climate regions, and the need for research in this field.